ANALISIS METODE PEMBELAJARAN MULTIMEDIA BERBASIS OBJECT – ORIENTED PROGRAMMING (ADOBE – FLASH) PADA MATA KULIAH ENGLISH FOR TOURISM - ambar wulan sari; Resty Wahyuni; Alfitriani Siregar (Fakultas Keguruan dan Ilmu Pendidikan, Universitas HKBP Nom- mensen, 2020)
The purpose of this study is (1) Is there an influence on the development of Adobe-Flash multimedia programs on the ability of students to improve vocabulary skills in English For Tourism courses ?. (2) What percentage of the influence of the development of multimedia programs on the ability of students to improve vocabulary skills in English For Tourism courses? This research is an experimental research. The program implementation technique for this research is a preliminary test used to measure students' vocabulary abilities of the material being taught while the final test is carried out to determine student learning outcomes after being treated using Multimedia-based Object-Oriented Programming (Adobe-Flash) learning methods in the eyes English for Tourism lecture. Key Words: Multimedia-Based Learning Method Object-Oriented Programming (Adobe-Flash), Vocabulary Skills, English for Tourism